Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/j.femsim.2005.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The influence of microbial metabolites on human intestinal epithelial cells and macrophages in vitro

Abstract: Microbial metabolites may influence the metabolic integrity of intestinal epithelial cells and induce mucosal immune responses. Therefore, we investigated the effects of the microbial metabolites butyrate, iso-valerate, and ammonium on Caco-2 cells and macrophages. Barrier functioning was determined by measuring transepithelial electrical resistance and basolateral recoveries of metabolites. The barrier function of Caco-2 cells remained intact after exposures. Basolateral recoveries ranged from 6.2% to 15.2%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Although these fatty acids have been studied for their role in intestinal motility, 28,29 considerably more studies have focused on butyrate for its role in nourishing the colonic mucosa and in the prevention of colon cancer 30 and also for its influence on cytokine production by immune cells, which has produced so far controversial results. 31,32 L-selectin levels are measured in serum or plasma as a marker of the L-selectin levels in lymphocytes and neutrophils. One early phase of atherosclerosis involves the recruitment of inflammatory cells from the circulation and their transendothelial migration.…”
Section: Discussionmentioning
confidence: 99%
“…Although these fatty acids have been studied for their role in intestinal motility, 28,29 considerably more studies have focused on butyrate for its role in nourishing the colonic mucosa and in the prevention of colon cancer 30 and also for its influence on cytokine production by immune cells, which has produced so far controversial results. 31,32 L-selectin levels are measured in serum or plasma as a marker of the L-selectin levels in lymphocytes and neutrophils. One early phase of atherosclerosis involves the recruitment of inflammatory cells from the circulation and their transendothelial migration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the trophic effects of butyrate on colonocytes both in vivo and in vitro. In vivo, butyrate plays a critical role in the homeostasis of the colonic epithelium (23)(24)(25). However, in vitro butyrate induces differentiation, inhibits cellular proliferation, and stimulates apoptosis in cultured colorectal cancer cells (26 -28).…”
Section: Effect Of Receptor Depletion On Clonogenic Survivalmentioning
confidence: 99%
“…These data indicate that anti‐inflammatory benefits of LKM512 yogurt are influenced by intestinal bacterial metabolites than intestinal bacterial cell components derived from altered large intestinal microbiota. To our knowledge, there is little information supporting the relationship between intestinal bacterial metabolites and host health; however, van Nuenen et al (2005) reported that intestinal microbial metabolites influenced the metabolic integrity of intestinal epithelial cells and mucosal barrier function. However, we do not deny that the recognition of bacterial cell components by TLRs plays a crucial role in host immune system, e.g.…”
Section: Resultsmentioning
confidence: 99%